2021
DOI: 10.1186/s12889-021-11649-0
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder-engaged research: strategies for the prevention and control of overweight and obesity in Kenya

Abstract: Background This study was done as part of a larger study that aims to identify the most impactful and cost-effective strategies for the prevention and control of overweight and obesity in Kenya. Our objective was to involve stakeholders in the identification of the strategies that would be included in our larger study. The results from the stakeholder engagement are analyzed and reported in this paper. Design This was a qualitative study. A one-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Research on the nutritional value of traditional diets in Kenya may be helpful in advocating for the retention of healthy traditional diets. 59 Research on how city and transport planning in Kenya can be used to create healthy neighbourhoods would guide formulation of policies that create a healthy environment for all. Since Kenya is still battling undernutrition in some populations, studies investigating how stunting impacts BMI levels in adulthood are key.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the nutritional value of traditional diets in Kenya may be helpful in advocating for the retention of healthy traditional diets. 59 Research on how city and transport planning in Kenya can be used to create healthy neighbourhoods would guide formulation of policies that create a healthy environment for all. Since Kenya is still battling undernutrition in some populations, studies investigating how stunting impacts BMI levels in adulthood are key.…”
Section: Discussionmentioning
confidence: 99%
“…A description of the stakeholders and engagement process is given elsewhere. 59 , 60 We thank the external reviewers and the editorial team for their review and great input.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…In this study, we applied the assessing cost-effectiveness (ACE) approach which has been developed as a priority setting tool that enables evidence-based decision making [ 27 , 28 ]. Stakeholder engagement was part of the due process and this has been reported elsewhere [ 26 ]. We used a lifetime horizon in our assessment and targeted the 2019 Kenya population modelled over their remaining lifetime.…”
Section: Methodsmentioning
confidence: 99%
“…Our selection of interventions for inclusion in this study was drawn from broad strategies identified in a stakeholder engagement process with policy makers in Kenya [ 26 ]. We asked the stakeholders to identify existing and new strategies they considered relevant and appropriate for the prevention and control of overweight and obesity in Kenya.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation